Four new Chlaenius species (Coleoptera: Carabidae: Chlaeniini) from Asia and a key to the species of subgenus Chlaenioctenus - Liu, Ye; Shi, Hongliang; Liang, Hongbin (Zootaxa, 2013)
Four new Chlaenius species are described from Asian region: C. cheni Liu & Liang sp. n., C. bodhidharma Liu & Liang sp. n., C. li Liu & Liang sp. n., and C. aodai Liu & Liang sp. n. Chlaenius langsonensis Kirschenhofer, 2008 is assigned from subgenus Ocybatus to Chlaenioctenus. Chlaenius (Chlaenioctenus) eneides Bates, 1892 is redescribed and lectotype is designated. A key to all species of the subgenus Chlaenioctenus is provided.